A narrow endemic plant: evaluating population dynamics and conservation strategies - Nerea Alvite; Elisa Gago Moldes; Sergio Roiloa; Rodolfo Barreiro (Oryx)
Iberodes littoralis subsp. gallaecica (Laínz) M. Serrano, R. Carbajal & S. Ortiz is a small annual plant endemic to dune systems in the north-west Iberian Peninsula. It is categorized as Endangered on the IUCN Red List and is a priority taxon under the EU Habitats Directive. Nevertheless, the only comprehensive census of this subspecies was conducted in 2009. Here we present the results of a new survey conducted in 2023 that adds a new location to its known range. Comparison with the previous census suggests that both the total population and area of occupancy have increased. However, these changes were not uniform across the range of the subspecies, with populations increasing at the northern and southern extremes and populations at central sites remaining stable or decreasing. Spatial differences in climate, anthropogenic pressures, plant performance and/or random fluctuations may explain these interpopulation variabilities. Given that the majority of populations are already located within the EU Natura 2000 network, we recommend that the current level of protection be maintained and that the plant be reintroduced into dune systems from which it has recently disappeared. Despite the increase in the total population, we recommend that the plant be recategorized as Critically Endangered given that its area of occupancy is small. Further censuses over time will be needed to provide information on population dynamics, trends, fluctuations and responses to environmental variables.